2015
DOI: 10.1016/j.ijsu.2015.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery (ERAS ® ) multimodal programme as experienced by pancreatic surgery patients: Findings from an Italian qualitative study

Abstract: According to the findings, uncomplicated pancreatic surgery patients may benefit from the ERAS programme. Preadmission counselling should help patients to assume an active role. Once the patient returns home, the availability of a caregiver should be thoroughly assessed to guarantee the support needed by patients to successfully complete the ERAS(programme. Surgery and nursing staff should carefully monitor patients and suggest whether they continue, interrupt, or individualise the scheduled ERAS interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(81 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Addressing information needs or providing information was the common theme across 24 (89%) of the 28 studies 8,11,20,21,23‐38,40‐42 . We identified that two topics tied as the second‐leading issues; 8 (29%) of the 28 studies included a common focus of addressing pain concerns when providing preoperative care, 17,22,25,27,28,35,36,41 and 8 (29%) of the 28 studies addressed preoperative fear and anxiety 17,19,25,28,35,37‐39 . The next most frequent issues addressed were the need for support (8 [29%] of the 28 studies), 8,17,22,26,28,32,38,39 patient satisfaction with the surgical experience (8 [29%] of the 28 studies), 20,23,29,31,34,35,37,38 and the need to make a decision (4 [14%] of the 28 studies) 19,26,30,34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Addressing information needs or providing information was the common theme across 24 (89%) of the 28 studies 8,11,20,21,23‐38,40‐42 . We identified that two topics tied as the second‐leading issues; 8 (29%) of the 28 studies included a common focus of addressing pain concerns when providing preoperative care, 17,22,25,27,28,35,36,41 and 8 (29%) of the 28 studies addressed preoperative fear and anxiety 17,19,25,28,35,37‐39 . The next most frequent issues addressed were the need for support (8 [29%] of the 28 studies), 8,17,22,26,28,32,38,39 patient satisfaction with the surgical experience (8 [29%] of the 28 studies), 20,23,29,31,34,35,37,38 and the need to make a decision (4 [14%] of the 28 studies) 19,26,30,34 …”
Section: Resultsmentioning
confidence: 99%
“…Galli et al 27 discussed the importance of establishing rapport between health care professionals and a patient preparing for surgery as an initial step in establishing trust. Based on this rapport, health care professionals can establish trust and build relationships that allow patients to have confidence that the health care team members will work to achieve positive outcomes 8,22,27,28,32,39 . The studies we reviewed also provided an important reminder that as part of establishing trust, health care professionals should always ensure privacy when communicating sensitive information 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, hospital duration and postoperative complications Clavien-Dindo stage I-II can be reduced by ERAS [41]. Accordingly, low-risk patients may benefit from the ERAS protocol [42]. Furthermore, our predictive models and nomograms allow for the opportunity to calculate the individual risk for the development of CR-POPF.…”
Section: Discussionmentioning
confidence: 99%